THE ROLE OF SOCIOLINGUISTICS IN LANGUNGE EDUCATION IN INDONESIA - Nopran Trias Permadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is entitled The Role of Sociolinguistics in Language Education in Indonesia. The method used The observational approach was used in this research to gather the data that would later be used to expound on the findings and draw conclusions. Sociolinguistics and the teaching of languages are intertwined in a variety of ways. Both the teaching of a language and the learning of a language are influenced by a variety of social circumstances. The link between sociolinguistics and language instruction is the topic of investigation in this particular piece of writing. There are a number of social aspects, including the circumstance, the context, and the social environment, which all play roles in language instruction. It demonstrates how effectively current education can take into consideration the primary aspects that impact language choices and discusses the main factors that influence linguistic choices. In addition to this, it studies the clear linguistic differences that exist between persons who belong to different sectors of society.